Controversies and future directions of endoscope in breast surgery - CAO Xuchen (Waike lilun yu shijian)
Laparoscopic surgery has been widely applied in various surgical fields, demonstrating its advantages in minimally invasive procedures. However, for breast surgery, which lacks natural cavities, there remain certain controversies and unresolved issues. This review summarized the background, development, challenges, and solutions regarding the endoscope in breast surgery, and discussed the theoretical and practical basis for its application. Endoscope will become a new iterative tool in the field of breast surgery and is expected to provide a safer and minimally invasive way to serve more patients.